The influence of various sized zircaloy-4 oxidation products on hydrogen generation of the water solution by Co-60 gamma radiolysis - Yoshinobu MATSUMOTO (The Japan Society of Mechanical Engineers, 2020)
In this work, we have experimentally studied the effect of particle size of the oxidized zircaloy-4 on the observed yield of Hydrogen generation by Co-60 gamma radiolysis of water. The oxidation products were obtained by high-temperature oxidation of zircaloy-4 under dry air atmosphere for 2 and 4 hours. We crushed them into various sizes from 3 to 484 μm after the oxidation. The crushed particles of the product of 4 hours oxidation consisted of almost monoclinic zirconium oxide and the 2 hours oxidation product contained from 26 to 56% of tetragonal zirconium oxide. These particles had specific surface areas from 0.73 to 2.58 m2/g and band gaps 5.1 eV all. The oxidation products of the weight fraction of 10% and distilled water were mixed into a 4 ml glass vial to examine the Hydrogen generation by Co-60 gamma radiolysis. The experiments have presented that the observed hydrogen yield, G(H2) was increased by decreasing the median particle diameter of both the oxidation products. Especially, the G(H2) of water added the particles with 3 or 5 μm became larger than that of only distilled water. This enhancement was not caused by the bandgap of the oxidation product. Calculated G(H2) per surface area of the oxidation product, G(H2)/S was constant on all particle sizes. Furthermore, G(H2)/S of the water added the oxidation products with the median particle diameter 3 or 5 μm were larger than the commercial zirconium oxides (m-ZrO2, t-ZrO2) whose median particle diameters are 3 μm. In conclusion, Hydrogen generation of water by Co-60 gamma radiolysis was influenced by the particle size added into water. We have considered that the surface area of the oxidation product was the predominant factor of this effect because the G(H2) per specific surface area was constant regardless of particle size of the crushed oxidation products in this experiment.